Designing and codifying a test to measure the accuracy of performing the scoring skill by jumping forward and some biomechanical variables after performing physical effort in handball - Shatnawi, M. M.; Aljadaan, D. A. s. N.; Al-Saeedin, M. S.; Al-Habashneh, F.; Al-Hasanat, O. A. (ResearchJet Journal of Analysis and Inventions, 2022)
The study aimed at designing and codifying a test to measure the accuracy of performing the scoring skill by jumping forward in handballto identify an index for the values of some biomechanical values in the skill of scoring among players. The study used the descriptive survey approach. The study sample consisted of players of the specialized school in handball for the sports season (2019-2020) with a total of (54) players. A test was designed to measure the accuracy of scoring forward in order to adopt it as a test for evaluating the performance of players and come up with accurate results in mechanical analysis, wherethe successful attempt is considered to find out the biomechanical variables. The main experiment was performed to the study sample using a video camera as well as (Kinovea-v18) related to analyzing the skills, while Data were processed using(SPSS -21). The new testing method confirmed its ability to determine imbalance points and improve scoring performance from the forward area. The testing method concluded a number of conclusions, including: 1- Designing and codifying a test to measure the accuracy of scoring from jumping forward and some biomechanical variables after the performance of physical effort in handball. 2- The highest level gained by the study sample individuals was within the medium range and the lowest level was medium.